Utilization of Learning Resources in Islamic Religious Education at Junior High Schools in Rejang Lebong Regency - Herwin Wijaya; Idi Warsah; Sutarto Sutarto; Indrayanto Indrayanto; Aida Rahmi Nasution (GHAITSA : Islamic Education Journal, 2026)
This research is motivated by the importance of optimizing learning resources in Islamic Religious Education (PAI) learning. The aim is to describe the empowerment of PAI learning resources at the junior high school level, focusing on their availability, utilization, and empowerment strategies by teachers. The study employs a descriptive qualitative method, conducted in 24 State Junior High Schools in Rejang Lebong Regency. Data were collected through interviews and observations of teachers, students, and relevant stakeholders. The findings indicate that: (1) The availability of learning resources is generally adequate but uneven across regions, with technological access still dependent on infrastructure and teacher competency; (2) The dominant learning resources used are textbooks, while the utilization of alternative sources such as the local environment and digital resources is not yet optimal; (3) Teacher empowerment strategies include integrative and contextual approaches, although their application is still limited. It is concluded that the empowerment of PAI learning resources in Rejang Lebong Regency has been implemented with various strategies, but still requires improvements in equitable access, teacher training, and optimization of non-traditional learning resources to enhance the quality of learning.